At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's solve the given problem step-by-step:
1. We are given two functions:
[tex]\[ h(x) = x^2 + 1 \][/tex]
[tex]\[ k(x) = x - 2 \][/tex]
2. We need to evaluate [tex]\(h(2)\)[/tex] and [tex]\(k(2)\)[/tex].
3. Calculate [tex]\(h(2)\)[/tex]:
[tex]\[ h(2) = 2^2 + 1 \][/tex]
[tex]\[ h(2) = 4 + 1 \][/tex]
[tex]\[ h(2) = 5 \][/tex]
4. Calculate [tex]\(k(2)\)[/tex]:
[tex]\[ k(2) = 2 - 2 \][/tex]
[tex]\[ k(2) = 0 \][/tex]
5. To find [tex]\((h + k)(2)\)[/tex], we add the values of [tex]\(h(2)\)[/tex] and [tex]\(k(2)\)[/tex]:
[tex]\[ (h + k)(2) = h(2) + k(2) \][/tex]
[tex]\[ (h + k)(2) = 5 + 0 \][/tex]
[tex]\[ (h + k)(2) = 5 \][/tex]
Therefore:
[tex]\[ (h + k)(2) = \boxed{5} \][/tex]
1. We are given two functions:
[tex]\[ h(x) = x^2 + 1 \][/tex]
[tex]\[ k(x) = x - 2 \][/tex]
2. We need to evaluate [tex]\(h(2)\)[/tex] and [tex]\(k(2)\)[/tex].
3. Calculate [tex]\(h(2)\)[/tex]:
[tex]\[ h(2) = 2^2 + 1 \][/tex]
[tex]\[ h(2) = 4 + 1 \][/tex]
[tex]\[ h(2) = 5 \][/tex]
4. Calculate [tex]\(k(2)\)[/tex]:
[tex]\[ k(2) = 2 - 2 \][/tex]
[tex]\[ k(2) = 0 \][/tex]
5. To find [tex]\((h + k)(2)\)[/tex], we add the values of [tex]\(h(2)\)[/tex] and [tex]\(k(2)\)[/tex]:
[tex]\[ (h + k)(2) = h(2) + k(2) \][/tex]
[tex]\[ (h + k)(2) = 5 + 0 \][/tex]
[tex]\[ (h + k)(2) = 5 \][/tex]
Therefore:
[tex]\[ (h + k)(2) = \boxed{5} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.